The Nexus of QAnon and COVID-19: Legitimation Crisis and Epistemic Crisis - Morelock, Jeremiah; Narita, Felipe Ziotti [UNESP] (SAGE Publications, 2022)
In this article, we analyze the role of conspiracy theories, especially the spread of QAnon during the COVID-19 pandemics, in the legitimation crisis and epistemic crisis in contemporary democracies. We discuss Habermas’ theory of legitimation crisis and the potential for reactionary movements in times of such crisis, as well as Hofstadter’s description of the paranoid style in political culture. We explain the notion of ‘epistemic crisis’ as theorized by Larry Laudan and discussed recently in relation to social media. We discuss anti-intellectualism in Hofstadter’s terms, and explain its connection with populism. Finally, we explain how all of this comes to bear on the contemporary proliferation of conspiracy theory, using QAnon and the COVID crisis as our point of reference, and examples from the United States and Brazil to illustrate our points. QAnon fueled COVID-19 conspiracy theories, and COVID-19 conspiracy theories rocketed QAnon to a place of major influence.
Keywords: conspiracy theories; conspiracy theory; COVID-19; crisis; epistemic crisis; legitimation crisis; populism; QAnon; social movements; sociology of knowledge